Tonalność języka w pieśni na podstawie utworów ludu Sui - Kupś, Hanna; Burkiewicz, Kamil (Investigationes Linguisticae, 2018)
This article aims at describing the realization of lexical tones in songs of Sui people. The main focus for research are the drinking and mountain songs, a part of Sui’s abundant oral literature, most commonly used during traditional festivities and social gatherings. The paper starts with the presentation of the state of current research and the description of Sui language and music. What follows is analysis of four Sui songs and conclusions. The methodology of the article is mostly based upon previous accomplishments, in eg. Chan 1987 and Wong & Diehl 2002.